ENHANCING STUDENTS’ WRITING SKILL THROUGH PROBLEM BASED LEARNING STRATEGY TO THE SECOND YEARSTUDENTS OF SMA NEGERI 2 BIREUEN - Misnawati Misnawati; Rizka Sylvia (Jurnal Pendidikan Almuslim, 2019)
The title of this research is Enhancing Students’ Writing Skill through Problem Based Learning Strategy to the Second Year Students of SMA Negeri 2 Bireuen (A Collaborative Classroom Action Research). Writing is one of the important skills to be mastered by the students in learning English. In reality, many students faced difficulties in expressing their ideas in writing. The researcher found the problems of the research: The first, How does PBL Strategy enhance the writing skill of the second year students of SMA Negeri 2 Bireuen? The second, How do the students respond toward the implementation of the PBL Strategy in writing skill at the second year students of SMA Negeri 2 Bireuen? Based on the problems above, the researcher put two purposes of this research: The first, to find out the PBL Strategy enhance the writing skill of the second year students of SMA Negeri 2 Bireuen. The second, to know the students’ responses toward the implementation of the PBL Strategy in writing skill at the second year students of SMA Negeri 2 Bireuen. To answer the questions above, the researcher used collaborative classroom action research (CAR) as the methodology of the research. The researcher conducted this research at SMA Negeri 2 Bireuen, and the subject of the research was class XI IIS 2 which consisted of 25 students. In collecting data, the researcher used some instruments such as test, observation checklist both for students and teacher, questionnaire and field notes. This research was done in two cycles. Each cycle consisted of four steps: planning the action, implementing the action, observing the action, and analyzing and reflecting. After the researcher did all steps of the research action (cycle I and cycle II), the students’ means score increased from 62.6 in cycle I and became 83.4 in cycle II. It meant that Problem Based Learning Strategy could improve the students` writing argumentative text. The students also had a good performance in the teaching-learning process. It could be seen from the result of the observation sheet, in the cycle I the average score of students' activities was 43.6%, while in the cycle II was 77.6%. Based on these results, the researcher concluded that this research was success. Key Words : Writing Skill, Problem Based Learning Strategy